Effect of some fungicide on growth (in mm) of Curvularia lunata, Fusarium equiseti, Phoma vulgaris and Botryodiplodia theobromae - S, Dandge V (Journal of Experimental Sciences, 2012)
Large number of crops, vegetables, fruits, are cultivated throughout the world .Due to different climatic conditions many difficulties and problems widely differing intervene the development in agriculture. Amongst these difficulties and problems the control of plant diseases is an important one. Fungi respond to various fungicides in their ability to grow and reproduce. However this aspect of fungal metabolism has been relatively less attended to. In the present investigation effects of different fungicides was studied on Curvularia lunata, Fusarium equiseti, Phoma vulgaris and Botryodiplodia theobromae.